P4_6 Buried Alive - Kerr, Tendayi; Adams, Nathan; Brewster, Nick; Smith, Jason (Physics Special Topics, 2011)
Situations in which a character in a film or TV program has been buried alive appear commonly, for example David Blaine was entombed for a week as an endurance feat. This paper calculates how long a human can survive in a casket without an external air or water supply. A value of 11 hours was calculated for a human perfectly at rest. A value of 41 minutes obtained if the human was distressed and respiring at the maximal rate. The length of time in the casket is determined by the human’s activity.